The quality of life, risk of abuse, and self-esteem of older adults in the Manawatu : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Psychology at Massey University - McDonald-Smith, Patricia Bridget (Massey University, 1997)
The aim of this study was to explore and investigate levels of quality of life, levels of self-esteem and risk for abuse in elderly New Zealanders, either living the community or in rest homes. Subjects were 50 individuals, aged 64 to 99 years, half of which were drawn by random sample from either private dwellings and city council accommodation in the community, or by convenience sample from the Royal New Zealand Foundation for the Blind. The other half was drawn by convenience sample from seven preselected rest homes in the region. Each subject was individually and personally interviewed by the researcher, and measures of quality of life using Cummins' Comprehensive Quality of Life questionnaire (ComQol-4; Cummins, 1993), of self-esteem using the Rosenberg Self-esteem Scale (Bachman, O'Malley & Johnston, 1978), and of risk for abuse using the Hwalek-Sengstock Elder Abuse Screening Test H/S-EAST (Neale, Hwalek, Scott, Sengstock & Stahl, 1991) were administered. Analysis of the results revealed that quality of life of Manawatu elders was found to be at a medium level. Satisfaction with quality of life was similar to Australian older adults, and elders were satisfied with all life areas studied, being most satisfied with interpersonal relationships and least satisfied with health. The level of self-esteem of elders was found to be low. The overall level of risk for abuse was found to be less than levels in overseas abused and comparison groups. Elderly persons living in the community had better objective quality of life than those living in rest homes. However, there were no differences between these two groups on perceived satisfaction with and importance of the various areas or domains contributing to quality of life, on self-esteem, or on risk for abuse. Implications of the results, methodological issues and future directions for New Zealand research were discussed.
Keywords: Older people, Palmerston North; Eldery social conditions; Elderly social networks; Elder abuse; Rest homes; Quality of life; Self-esteem